2015
DOI: 10.1016/j.dcn.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Producing morphologically complex words: An ERP study with children and adults

Abstract: A widely studied morphological phenomenon in psycholinguistic research is the plurals-inside-compounds effect in English, which is the avoidance of regular plural modifiers within compounds (e.g., *rats hunter). The current study employs event-related brain potentials (ERPs) to investigate the production of plurals-inside-compounds in children and adults. We specifically examined the ERP correlates of producing morphologically complex words in 8-year-olds, 12-year-olds and adults, by recording ERPs during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 36 publications
6
17
1
Order By: Relevance
“…The negativity of interest has been reported in four previous studies [ 21 , 22 , 23 , 24 ] which all showed a frontally distributed effect. Visual inspection of the data confirmed a similar distribution in the present study.…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…The negativity of interest has been reported in four previous studies [ 21 , 22 , 23 , 24 ] which all showed a frontally distributed effect. Visual inspection of the data confirmed a similar distribution in the present study.…”
Section: Methodssupporting
confidence: 61%
“…We note that the account proposed here for the negativity obtained for analytic comparatives also applies to the results of production studies that tested other phenomena of morphological encoding. Recall that Budd et al (2013) [ 21 ] and Festman and Clahsen (2016) [ 22 ] obtained this enhanced negativity for the production of regular past tense forms, Jessen et al (2016) [ 24 ] for regular participles in German, and Budd et al (2015) [ 23 ] for regular plurals inside compounds in English. What is common to the phenomena that elicited this negativity is that they involve grammatically-based computational processes that have to be prevented from over-application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Items were presented on a 15-inch computer screen using Presentation (version 14.9 07.09.11), positioned approximately 100cm apart from participants. All other procedures followed the same as in Budd et al (2013Budd et al ( , 2015 and Jessen et al (2017). Each trial began with a fixation cross at the centre of the screen presented for 100ms, followed by the infinitive/stem form (e.g., to walk/…sag…) presented in Comic Sans font (96-point) in black on a white background, lasting 1,000ms.…”
Section: Methodsmentioning
confidence: 99%
“…This technique provides two sets of data: (i) children's (delayed) overt spoken output of a targeted morphologically complex word form, and (ii) the corresponding ERPtime-locked to a silent production cueto allow insights into the encoding and planning of this word form prior to overt articulation. Using this paradigm, Budd et al (2013) examined past tense formation in English, Budd et al (2015) plural forms in English compounds, and Jessen et al (2017) past participle formation in German. These studies tested seven-to thirteen-year-old children (and adults) and yielded consistent results.…”
Section: Morphological Encoding In Adults and Childrenmentioning
confidence: 99%